Native and Nonnative Crocodilians of Florida - Michiko A. Squires; Seth C. Farris; Brian M. Jeffery; Frank J. Mazzotti (EDIS)
Florida has two native species of crocodilians, the American alligator and the American crocodile. These federally protected species are easily confused with nonnative crocodilians found in south Florida, such as the spectacled caiman and the Nile crocodile. Some key features used to distinguish these animals are the shape of the head, the shape of the snout, and the pattern of nuchal scutes (bony plates in between head and shoulders). It is important to report all nonnative crocodilians so that researchers may quickly remove them in order to protect Florida’s native ecosystems. This 2-page fact sheet was written by Michiko A. Squires, Seth C. Farris, Brian M. Jeffery, and Frank J. Mazzotti, and published by the UF Department of Wildlife Ecology and Conservation, September 2013.